HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU PENCEGAHAN COVID 19 PADA SISWA/I KELAS IV VI SD XYZ - Christopher Tan; Ecie Budiyanti (Atma Jaya Catholic University of Indonesia, 2022)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has been a great issue for people throughout Indonesia, including elementary students. Although most confirmed cases of COVID-19 in children are reported as asymptomatic or mild, children infected with SARS-CoV-2 are still prone to complications or worsening. Until now, there is still a lack of research on the relationship between knowledge and prevention practice regarding COVID-19 among elementary students. The purpose of this research is to find out the relationship between knowledge and prevention practice regarding COVID-19 among grade 4-6 students at XYZ Elementary School. Methods: A descriptive analytical research with a cross-sectional study towards 297 grade 4-6 students at XYZ Elementary School. Inclusion criteria include active students of XYZ Elementary School, willing to participate and have gotten permission from teacher/parents/guardian through informed consent. Exclusion criteria include students who are not present during research, do not understand Indonesian and English as well as having mental and emotional disabilities. Data in this research was acquired through a questionnaire. Data analysis was conducted using Chi-square test. Results: Most of the respondents, as many as 194 respondents (65.3%), have a low level of knowledge. Most of the respondents, as many as 141 respondents (47.5%), have good prevention practice regarding COVID-19. Analysis with Chi-square test showed a significant relationship between knowledge and prevention practice regarding COVID-19 (p<0.001). Conclusion: There is a significant relationship between knowledge and prevention practice regarding COVID-19 among grade 4-6 students at XYZ Elementary School. Key Words: COVID-19, elementary students, knowledge, practice, prevention